Factors associated with ergot resistance in pearl millet - and S.B. KING, R.P. THAKUR, V.P. RAO (Indian Phytopathology, 2002)
The host and host-pathogen interaction factors associated with resistance to ergot (Claviceps fusiformis) was studied in resistant, intermediate and susceptible cultivars of pearl millet. Protogyny, time between full protcgyny and anthesis initiation, and stigma length were significantly shorter and seed set was significantly higher in the resistant and intermediate culiivars than in the susceptible cultivars. Latent periods were comparable in the three groups of cultivars, but the sporulation period, ergot severity, and numbers of conidia and sclerotia produced were significantly lower in the resistant and intermediate than in the susceptible cultivars. Implications of these findings in ergot epidemiology and management are discussed.